2016
DOI: 10.1016/j.ypmed.2015.12.017
|View full text |Cite
|
Sign up to set email alerts
|

Effect of appreciation for Indigenous cultures and exposure to racial insults on alcohol and drug use initiation among multiethnic Argentinean youth

Abstract: This study evaluated the effect of factors reflecting appreciation of Indigenous culture and racial insults on alcohol and drug use initiation among multi-ethnic youth in Jujuy, Argentina. Students were surveyed from 27 secondary schools that were randomly selected to represent the province. A total of 3,040 eligible students in 10th grade, age 14 to 18 years were surveyed in 2006 and 2,660 of these same students completed surveys in 11th grade in 2007. Multivariate logistic regression models assessed the effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
2
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 50 publications
2
2
0
3
Order By: Relevance
“…Almost 40% of Colombian adolescents in the current study experienced ethnic-racial-based discrimination at least once in the last year. This prevalence estimate is similar to another study in Latin America that surveyed adolescents about ethnic-racial discrimination (i.e., Argentina; Alderete et al, 2016). Further, consistent with our hypothesis and studies of youth in other countries (Marks et al, 2015), the frequency with which youth experienced ethnic-racial discrimination corresponded with concurrently lower self-esteem and elevated depressive symptoms.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Almost 40% of Colombian adolescents in the current study experienced ethnic-racial-based discrimination at least once in the last year. This prevalence estimate is similar to another study in Latin America that surveyed adolescents about ethnic-racial discrimination (i.e., Argentina; Alderete et al, 2016). Further, consistent with our hypothesis and studies of youth in other countries (Marks et al, 2015), the frequency with which youth experienced ethnic-racial discrimination corresponded with concurrently lower self-esteem and elevated depressive symptoms.…”
Section: Discussionsupporting
confidence: 89%
“…The negative developmental implications of ethnic-racial-based discrimination have been well-documented in studies of adolescents in the U.S. (Benner et al, 2018; Yip et al, 2019). Research has also identified ethnic-racial discrimination as a risk factor related to poorer psychosocial adjustment and health among adolescents in other countries (e.g., Alderete et al, 2016; Schachner et al, 2018; also see Marks et al, 2015, for review). For example, experiencing racial insults was associated with increased risk for binge drinking in a multiethnic-racial sample of adolescents in Argentina (Alderete et al, 2016).…”
Section: Extending the Risk And Resilience Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…Já os altos níveis de apreciação de culturas indígenas reduziram pela metade ou menos as chances de uso de outras drogas como maconha, cocaína ou inalantes, mas a exposição a insultos raciais aumentou a probabilidade de consumo excessivo de álcool. Desse modo, promover a valorização de culturas e reduzir os insultos raciais são objetivos a serem incorporados em programas de prevenção ao uso de substâncias psicoativas entre jovens indígenas 21 .…”
Section: Estudos Em Saúdeunclassified
“…3 En Argentina, la prevalencia de consumo de inhalables creció de 0.9% en 2001 al 4.5% en 2011. 4 Por otro lado, una revisión de la literatura internacional sobre la epidemiología del consumo de solventes inhalables indica que ésta es una práctica frecuente entre los jóvenes de países como Brasil, México, Paraguay, Chile, Colombia, Nicaragua, España, Canadá, Nueva Zelanda y Australia. 5 En México, las investigaciones realizadas han permitido identificar variaciones en el comportamiento de este fenómeno a través de los años; por ejemplo, en la década de 1970 y 1980 los inhalables y la mariguana eran las principales drogas consumidas en nuestro país, posteriormente, hacia el año de 1997 fueron sustituidas por la cocaína que ocupó el primer lugar de preferencia en ambos casos, sin incluir alcohol y tabaco.…”
Section: Antecedentesunclassified